The galactolipid monogalactosyldiacylglycerol (MGDG) contributes to photosynthesis-related processes in Arabidopsis thaliana - Aronsson, Henrik (Landes Bioscience, 2008)
Processes putatively dependent on the galactolipid monogalactosyldiacylglycerol (MGDG) were recently studied using the knockdown monogalactosyldiacylglycerol synthase 1 (mgd1-1) mutant (∼40% reduction in MGDG). Surprisingly, targeting of chloroplast proteins was not affected in mgd1-1 mutants, suggesting they retain sufficient MGDG to maintain efficient targeting. However, in dark-grown mgd1-1 plants the photoactive to photoinactive protochlorophyllide (Pchlide) ratio was increased, suggesting that photoprotective responses are induced in them. Nevertheless, mgd1-1 could not withstand high light intensities, apparently due to impairment of another photoprotective mechanism, the xanthophyll cycle (and hence thermal dissipation). This was mediated by increased conductivity of the thylakoid membrane leading to a higher pH in the thylakoid interior, which impaired the pH-dependent activation of violaxanthin de-epoxidase (VDE) and PsbS. These findings suggest that MGDG contribute directly to the regulation of photosynthesis-related processes.